Dampak akut pengunaan foam rolling sebelum pemanasan terhadap kinerja eksplosif atlet futsal kota semarang - Mohamad Alfarizi; Indra Ramadhan; Hadi Hadi (Jurnal Porkes, 2026)
The use of foam rolling before dynamic warm-ups is common among futsal athletes; however, its acute effects on explosive performance a key requirement of futsal remain unclear, and previous research findings have been inconsistent. This study aims to analyze the acute effects of foam rolling before dynamic warm-ups on the explosive performance of futsal athletes. Research Method: A total of 18 male futsal athletes (age 20.0 ± 0.75 years) were randomly assigned to a control group (Faststart warm-up) and an experimental group (foam rolling + Faststart) using a randomized pretest-posttest control group design. Explosive performance was measured via the vertical jump test, 20-meter sprint, and T-test. Research results: Lower-body power increased but not significantly (control: p=0.066; experimental: p=0.223). Sprint time decreased significantly in both groups (control: p=0.004; experimental: p<0.001), with a greater improvement in the experimental group. Agility improved significantly in both groups (control: p=0.010; experimental: p=0.015), though the control group showed better results. In conclusion, foam rolling before dynamic warm-up produces varying acute effects on each component of explosive performance and is not recommended as a primary strategy in warm-up to comprehensively enhance the explosive performance of futsal athletes.